HUBUNGAN ANTARA KREDIBILITAS PETUGAS PELAYANAN INFORMASI PUSKESMAS DENGAN SIKAP PENGUNJUNG TERHADAP PUSKESMAS NAGREG - Sumiyati, Iin; Komala, Lukiati; Setianti, Yanti (Communication, 2018)
One of the most essential community services is the health-care service. Since, basically everyone needs a healthy physic to run all activities, so he could live his daily life well. Therefore, the best and trustworthy health-care service for community is essentially needed. The purpose of this research is to reveal the relation of the Informational service officers5' skills, interests, and trusts on patients/visitors' attitude toward the Local Integrated Service Unit of the Community Health Clinics in Nagreg. For the research, writer used the Correlational Quantitative Method, which is revealing the relation between one variable with the others. The result of the research shown that there's a significant relationship between the Informational service officers' skills, on patients/visitors' attitude toward the Local Integrated Service Unit of the Community Health Clinics in Nagreg. Which means that the higher skill of the Informational service officers have, the better attitude will be shown by the patients/visitors in the Local Integrated Service Unit of the Community Health Clinics in Nagreg. The officers' appeals can also increase the patients/visitors' positive attitude. And also, the more trustworthy the officers are, the more positive attitude will be shown by the patients/visitors toward the Informational service in the Local Integrated Service Unit of the Community Health Clinics in Nagreg.